1978
DOI: 10.1515/cclm.1978.16.9.503
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone Binding Proteins in Normal Human Myometrium and Leiomyoma Tissue

Abstract: Summary: The occurrence and characteristics of macromolecular components of normal human myometrium and leiomyoma which bind [ 3 H]estradiol and [ 3 H]progesterone were investigated, employing dextran coated charcoal, density gradient centrifugation and gel filtration techniques.On sucrose density gradient centrigugation, [ 3 H]progesterone was bound by macromolecules with sedimentation rates of about 4 S and 8 S.The major [ 3 H]progesterone binding component had a sedimentation coefficient of about 4 S, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
(24 reference statements)
1
18
1
Order By: Relevance
“…A possible explana tion was suggested by Pollow et al [6] who found that the activity of (3-hydroxysteroid dehydrogenase, which converts 17 p-estradiol to estrone, a much less potent estrogen, is lower in myomas than in surrounding muscle. These authors also found a higher estradiol-binding capacity and a lower concentration of progesterone receptors in myoma, as compared to normal myometrium [7], These findings could well explain increased estrogen effect on myomas even when the prevailing hormonal environment is low in estrogens.…”
Section: Discussionmentioning
confidence: 75%
“…A possible explana tion was suggested by Pollow et al [6] who found that the activity of (3-hydroxysteroid dehydrogenase, which converts 17 p-estradiol to estrone, a much less potent estrogen, is lower in myomas than in surrounding muscle. These authors also found a higher estradiol-binding capacity and a lower concentration of progesterone receptors in myoma, as compared to normal myometrium [7], These findings could well explain increased estrogen effect on myomas even when the prevailing hormonal environment is low in estrogens.…”
Section: Discussionmentioning
confidence: 75%
“…it was inferred that the receptors were biochemically similar in both tissues. Work by Pollow et al 17 on sedimentation patterns as well as elution profiles in agarose , showing that the properties of the receptors in leiomyoma and myometrium are similar. supports this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the studies reviewed, the concentrations of both the ERs and PRs were greater in leiomyomata than the myometrium Brandon et al 1993Brandon et al , 1995Buchi and Keller 1983;Eiletz et al 1980;Englund et al 1998;Kawaguchi et al 1991;Lessl et al 1997;Marugo et al 1989;Nisolle et al 1999;Otsuka et al 1989;Pollow et al 1978a;Puukka et al 1976;Rein et al 1990c;Sadan et al 1987;Soules and McCarty 1982;Tamaya et al 1979Tamaya et al , 1985Vij et al 1990;Viville et al 1997;Vollenhoven et al 1994;Wilson et al 1980). In addition, Sadan et al found the ER and PR to be elevated in fibroids during all phases of the menstrual cycle when compared with matched myometria (Sadan et al 1987).…”
Section: Laboratory Studiesmentioning
confidence: 98%